DISEMINASI TEKNOLOGI FORMULATED DIET ALTERNATIF DALAM UPAYA MENINGKATKAN PRODUKTIVITAS BUDIDAYA IKAN NILA INTENSIF - Efrizal, Efrizal; Nurmiati, Nurmiati; Agustien, Anthoni; Syam, Zuhri; Suwirmen, Suwirmen; Zakaria, Indra Junadi; Rusnam, Rusnam; Deswati, Deswati (Jurnal Hilirisasi IPTEKS, 2021)
Fish cultivators generally experience difficulties providing quality artificial feed (pellets) due to a lack of knowledge and skills in processing technology and making alternative feeds. Besides that, the costs incurred for feed procurement are relatively large, reaching 70 - 80% of the total production costs. However, the provision of feed is often an obstacle because, in addition to the increasingly high price, the quality of available feed does not always match the nutritional needs needed by Fish. The provision of quality feed for intensively cultivated tilapia dramatically affects the resulting growth and productivity. The higher the quality of the feed, the production will also increase. One of the technologies that can be applied to overcome this problem is the manufacture of alternative formulated diets using local raw materials. The method used in this service activity is the transfer of knowledge presented in the socialization activities in the form of 1) introduction to the types of alternative fish feed ingredients sourced from the area, (2) preparation of artificial tilapia feed formulations, (3) manufacturing technology artificial feed (pellets) and 4) monitoring and assistance. The socialization was carried out in the form of a lecture and was followed by a question and answer session. The results of farmer activities recognize the types of local feed that can be used as fish feed, know the preparation of feed formulations, and alternative artificial feed manufacturing technologies. The knowledge and skills possessed by fish cultivators are expected to overcome the difficulties of fish farmers in providing feed so that fish production and cultivation business increase.